Improving Student Learning Outcomes With Educational Game-Based Interactive Learning Media - Suri, Atika; Novriana, Nadia; Susanti, Dela (International Journal of Education and Teaching Zone, 2022)
This study uses research and development methods (Research and Development) to produce an interactive learning device based on good educational games to improve student learning outcomes and motivation. This research is used in order to produce a certain product and test its effectiveness in improving student learning outcomes. Data processing using a questionnaire method, tests, then analyzed quantitatively descriptive. The research sample is MTs students. Tarbiyah Islamiyah Kedemangan class IX. The sampling technique used is purposive sampling, using quantitative, qualitative descriptive analysis, and correlative hypothesis testing. The results of this study showed an increase in student learning outcomes of the experimental group, which were classified as good by utilizing interactive media based on the Kahoot! Educational game. Not only that, but students' learning motivation is also categorized as good, so it can be concluded that interactive learning based on the educational game media that was developed is suitable to be used to improve student learning outcomes and motivation